Physicochemical Properties and Sensory Evaluation of Wheat-Mocaf-Based Dried Noodles Enriched with Catfish Bone Flour (Clarias sp.) - Brigitta Laksmi Paramita; Latif Sahubawa; Susana Endah Ratnawati (Indonesian Food and Nutrition Progress, 2021)
Fishbone is one of industrial waste that can be used as a calcium source. This study aims to find out the use of catfish bone flour as a calcium source in dried noodles, its effects on physicochemical and sensory evaluation of dried noodles, and the contribution of calcium-enriched dried noodles to the Indonesian Recommended Dietary Allowance (RDA) of calcium. The physicochemical properties (moisture, ash, protein, fat, carbohydrate, calcium, phosphor, water absorption, cooking loss, and extensibility) and sensory evaluation of dried noodles enriched with catfish bone flour in several variations (0%, 2%, 4%, 6%, 8%, and 10%) were investigated. Catfish bone flour significantly increased protein, fat, calcium, and phosphor content yet significantly decreased the moisture content, cooking loss, extensibility, and consumer acceptance (appearance and taste) of dried noodles. Dried noodles enriched with catfish bone flour had a calcium-phosphor ratio of 1:2 to 2:1. Dried noodles with the catfish bone flour level of 2% seemed to be the most efficient formulation with the Indonesian RDA contribution of 45.8% in serving size of 70g.